2014
DOI: 10.1111/acem.12539
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effects of a Brief Intervention to Increase Chlamydia and Gonorrhea Testing Uptake Among Young Adult Female Emergency Department Patients

Abstract: Objectives: The objective of this study was to test the effect of a brief educational and counseling intervention on increasing the uptake of free testing for Chlamydia trachomatis (chlamydia) and Neisseria gonorrhea (gonorrhea) among young female emergency department (ED) patients. Women are particularly vulnerable to more serious consequences of these infections due to asymptomatic presentation. Increased testing is important to detect, treat, and halt the spread of these infections among asymptomatic women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…8,18 It has also been demonstrated that female providers are more likely to screen for STIs than male providers. 18 Although some previous studies have shown parental presence to be a barrier to STI screening, 19,20 others have not demonstrated that effect. 8,21 This study did not examine the effect of parental presence on obtaining a history or screening for STIs.…”
Section: Discussionmentioning
confidence: 98%
“…8,18 It has also been demonstrated that female providers are more likely to screen for STIs than male providers. 18 Although some previous studies have shown parental presence to be a barrier to STI screening, 19,20 others have not demonstrated that effect. 8,21 This study did not examine the effect of parental presence on obtaining a history or screening for STIs.…”
Section: Discussionmentioning
confidence: 98%
“…SBIRT is based on behavior change communication (BCC) and motivational interviewing (MI), which is applicable to a wide spectrum of harmful behaviors such as high-risk sexual behavior, unhealthy food habits, and lifestyle (38,39). BI has been found to be acceptable but with variable effectiveness in promoting screening for sexually transmitted diseases (40,41). Randomized clinical trials on SBI have targeted both alcohol use and other risk behaviors such as high-risk sexual behavior, HIV-risk behaviors, and aggression.…”
Section: Expanding the Scope Of Brief Intervention To Target The Riskmentioning
confidence: 99%